Il recupero del sé attraverso l'autobiografia - Barbara Sandrucci (Strumenti per la didattica e la ricerca, 2005)
The request for a precise definition of memory would put any serious academic into difficulty. To provide a synthetic response, we could define memory as a marvellous mechanism, a means for taking us back in time. Memory is, therefore, a mental activity which connects us over time and gives a meaning to existence. Telling one's story, one's autobiography, signifies primarily taking stock of the state of one's own identity; it signifies communication, communicating who we are to ourselves and others. It means transforming the interior monologue into dialogue with the other; it means scanning and modulating our emotions through the representation of the events of our lives.